Hubungan Aktivitas Fisik dan Kualitas Tidur dengan Tingkat Stres pada Mahasiswa Asrama di STIKes Persada Husada Indonesia (PHI) Tahun 2025: Ida Safitri, Yuniar Rahmah, Herlina - Ida Safitri; Yuniar Rahmah; Herlina Herlina (Jurnal Persada Husada Indonesia, 2025)
Dormitory-based students frequently encounter academic and social pressures that may elevate stress, whereas habitual physical activity and sleep quality are presumed to play protective roles. This study examined the associations of physical activity and sleep quality with stress levels among dormitory students at STIKes Persada Husada Indonesia in 2025. A cross-sectional design with total sampling yielded 69 participants. Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ), sleep quality with the Pittsburgh Sleep Quality Index (PSQI; scores >5 indicate poor sleep), and stress with the stress subscale of the DASS-42. Bivariable analyses employed Chi-square tests with Cramer’s V and Spearman correlations at α=0.05. Results indicated significant associations between stress and age (p=0.007), physical activity (p=0.030), and sleep quality (p=0.007), whereas sex was not associated with stress (p=0.966). Descriptively, students reporting moderate-intensity physical activity were more likely to fall within the normal stress category, while poor sleep quality tended to be associated with moderate-to-severe stress. These findings underscore the relevance of promoting consistent moderate-intensity physical activity and sleep hygiene in dormitory settings as both preventive and supportive measures. Practical implications include structured fitness programs, stress-management education, and academic scheduling that preserves recovery time. In conclusion, fostering moderate levels of physical activity alongside improving sleep quality may contribute to lower stress among dormitory students and merits consideration in student welfare policies.